Who's declining the “free lunch”? New evidence from the uptake of public child dental benefits - Huong, Le; Nguyen, Ha; Luke, Connelly (My University, 2021)
This study provides the first evidence on the determinants of uptake of two recent public dental benefit programs for Australian children and adolescents from disadvantaged families. Using longitudinal data from a nationally representative survey linked to administrative data with accurate information on eligibility and uptake, we find that only a third of all eligible families actually claim their benefits. We provide new and robust evidence consistent with the idea advanced by recent economic literature that cognitive biases and behavioral factors are barriers to uptake. For instance, mothers with worse mental health or riskier lifestyles are much less likely to claim the available benefits for their children. These barriers to uptake are particularly large in magnitude: together, they reduce the uptake rate by up to 10 percentage points (or 36%). We also find some indicative evidence that a lack of information is a barrier to uptake.
Health Economics
Keywords: Adolescents and youth; Disadvantage, adversity and resilience; Childhood and child development; Families and relationships; Government, law and policy; Health and wellbeing; Income, wealth and finances; Intergenerational transfer; Lifestyle